Taking the Test: A Qualitative Analysis of Cultural and Contextual Factors Impacting Neuropsychological Assessment of Xhosa-Speaking South Africans. (25th November 2020) - Aghvinian, Maral; Santoro, Anthony F; Gouse, Hetta; Joska, John A; Linda, Teboho; Thomas, Kevin G F; Robbins, Reuben N
Abstract: Objective: There is an urgent need to make neuropsychological (NP) testing more acceptable, accessible, and culturally salient, particularly for culturally, educationally, and linguistically diverse individuals from countries who may have little-to-no experience with NP testing. In settings with limited resources such as South Africa, unique cultural and contextual factors (e.g., structural inequality, poverty) may impact the experience of NP evaluation. Research in this area is limited and requires further exploration. This qualitative study explores the role of cultural and contextual factors that may impact the experience of NP evaluation in a sample of Xhosa-speaking South African adults. Participant interviews explored the context from which individuals arrived at the NP assessment (e.g., quality of education, understanding of cognitive disorders), and their experience of completing NP tests. Method: This qualitative study used data from semistructured interviews to conduct a thematic analysis exploring contextual factors and the experience of completing NP tests for the first time among Xhosa-speaking South African adults ( N  = 22). Results: Although no participants had prior experience with NP testing, most found testing procedures acceptable. Most participants, however, reported a limited understanding of the purpose of NP testing and cognitive problems. Additionally, some participants reported perceptions and attitudes that could affect test performance, such as misinterpreting standard testing procedures (e.g., no feedback from the examiner, being stopped mid-task) as indicative of poor performance. Conclusions: This study provided much needed exploration into unique cultural factors that may impact the experience of NP assessment in South Africa, which could bias test performance and interpretation, and may aid the field of cross-cultural NP in better serving culturally and linguistically diverse populations. In these countries, neuropsychologists may need to actively evaluate participants' understanding of NP testing to help foster optimal assessment conditions. They may also need to educate participants on possible causes of cognitive disorders.